2015
DOI: 10.1016/j.bonr.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D3-supplementation on bone markers (serum P1NP and CTX): A randomized, double blinded, placebo controlled trial among healthy immigrants living in Norway

Abstract: ObjectiveVitamin D is essential for the maintenance of calcium homeostasis and bone mineralization; and low serum 25-hydroxyvitamin D (s-25-(OH)D) concentrations are associated with increased bone turnover. However, there is a lack of randomized controlled trials that have investigated the effect of vitamin D treatment on bone turnover in immigrant populations. We aimed to investigate the effect of 16-week daily vitamin D3 supplementation on bone formation marker serum procollagen type 1 amino-terminal propept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Trials investigating the relationship between vitamin D supplementation and CTX or P1NP have also shown mixed results, and to our knowledge, only a single small study has explored this relationship in hip fracture patients. [23][24][25][26] Our results demonstrate the relationship between baseline serum 25(OH)D and CTX and P1NP after hip fracture and confirm that observed trends in these BTMs after long bone fractures are similar in elderly hip fractures. We demonstrated that peak CTX and P1NP levels occur between 2-and 6-month postfracture, and that mean CTX and P1NP remained slightly elevated at 12 months (0.59 ng/ml and 63.1 mg/L, respectively) when compared to older adults without fractures.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Trials investigating the relationship between vitamin D supplementation and CTX or P1NP have also shown mixed results, and to our knowledge, only a single small study has explored this relationship in hip fracture patients. [23][24][25][26] Our results demonstrate the relationship between baseline serum 25(OH)D and CTX and P1NP after hip fracture and confirm that observed trends in these BTMs after long bone fractures are similar in elderly hip fractures. We demonstrated that peak CTX and P1NP levels occur between 2-and 6-month postfracture, and that mean CTX and P1NP remained slightly elevated at 12 months (0.59 ng/ml and 63.1 mg/L, respectively) when compared to older adults without fractures.…”
Section: Discussionsupporting
confidence: 83%
“…The relationship between serum 25(OH)D and CTX or P1NP has provided mixed results, and none have evaluated this trajectory in a fracture population. Trials investigating the relationship between vitamin D supplementation and CTX or P1NP have also shown mixed results, and to our knowledge, only a single small study has explored this relationship in hip fracture patients …”
Section: Discussionmentioning
confidence: 99%
“…Since vitamin D is a well-established bone nutrient, markers of bone formation and turnover have been considered indicators of long-term vitamin D status [21]. A high bone turnover in vitamin D-deficient individuals has been reported in observational studies [22]. However, relatively limited and inconsistent data are available regarding the separate effects of vitamin D on bone turnover markers in different populations of both sexes [17,18,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A high bone turnover in vitamin D-deficient individuals has been reported in observational studies [22]. However, relatively limited and inconsistent data are available regarding the separate effects of vitamin D on bone turnover markers in different populations of both sexes [17,18,[22][23][24]. Only one intervention study examined the effect of vitamin D supplementation alone on bone turnover in postmenopausal women [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that significant changes in biomarkers of bone turnover are not always evident, despite an observed increase in 25-(OH)D levels and concomitant decrease in PTH levels when administering supplementation with oral VitD. 76,77 As has been reported by others, 78,79 a negative correlation between 25-(OH)D levels and glucose, triglycerides and total cholesterol was apparent in our population, confirming that higher serum concentrations of 25-(OH)D tend to be associated with a more favorable lipid profile. Literature reports on the association between VitD and total cholesterol are often discrepant, even when extensive adjustments for confounding factors (particularly BMI) have been applied, 45,80,81 while the association between VitD and triglycerides is consistently reported as negative, 82 with two exceptions concerning adolescent girls.…”
Section: 55mentioning
confidence: 99%